Critiques of digital tools in agriculture: Challenges and opportunities for using digital tools to scale agroecology by smallholders - Shelton, Sadie W.; Gehan, Charlotte; Wollenberg, Eva Karoline; Costa, Ciniro; Burns, Sessie A.; Rowland, Bailey (2022)
KEY MESSAGES ◼ Two themes manifest in the challenges outlined, unequal power relations and a disconnect from farmers’ needs and input. ◼ Agricultural digitization should strive to follow ethical principles specific to the sector, agroecology offers an existing framework. ◼ Digital technical assistance that advances the interests of smallholders and is relevant to their farms can facilitate a shift towards agroecology through farmer-to-farmer networks and knowledge exchange. ◼ Recommendations include: ▪ Govern for an inclusive digital ecosystem & economy ▪ Leverage and expand food, data & social justice movements ▪ Code ethics into digital development